Molecular mechanism of IKK catalytic dimer docking to NF-κB substrates - Li, Changqing; Moro, Stefano; Shostak, Kateryna; O’Reilly, Francis J.; Donzeau, Mariel; Graziadei, Andrea; McEwen, Alastair G.; Desplancq, Dominique; Poussin-Courmontagne, Pierre; Bachelart, Thomas; Fiskin, Mert; Berrodier, Nicolas; et al. (Nature communications, 2024)
The inhibitor of κB (IκB) kinase (IKK) is a central regulator of NF-κB signaling. All IKK complexes contain hetero- or homodimers of the catalytic IKKβ and/or IKKα subunits. Here, we identify a YDDΦxΦ motif, which is conserved in substrates of canonical (IκBα, IκBβ) and alternative (p100) NF-κB pathways, and which mediates docking to catalytic IKK dimers. We demonstrate a quantitative correlation between docking affinity and IKK activity related to IκBα phosphorylation/degradation. Furthermore, we show that phosphorylation of the motif’s conserved tyrosine, an event previously reported to promote IκBα accumulation and inhibition of NF-κB gene expression, suppresses the docking interaction. Results from integrated structural analyzes indicate that the motif binds to a groove at the IKK dimer interface. Consistently, suppression of IKK dimerization also abolishes IκBα substrate binding. Finally, we show that an optimized bivalent motif peptide inhibits NF-κB signaling. This work unveils a function for IKKα/β dimerization in substrate motif recognition. The inhibitor of kB kinase (IKK) is a central regulator of NF-kB signalling. Here the authors identify a motif conserved in substrates of canonical and alternative NF-kB pathways which mediates docking to catalytic IKK dimers: they show that phosphorylation of the conserved tyrosine suppresses the docking interaction.